2010
DOI: 10.1007/s10495-010-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 triggers a TPCK-sensitive protease pathway leading to degradation of the BH3-only protein puma

Abstract: The protein Puma (p53-upregulated modulator of apoptosis) belongs to the BH3-only group of the Bcl-2 family and is a major regulator of apoptosis. Although the transcriptional regulation of Puma is clearly established, little is known about the regulation of its expression at the protein levels. We show here that various signals--including the cytokine TGFβ, the death effector TRAIL or chemical drugs such as anisomycin--downregulate Puma protein levels via a novel pathway based on the sequential activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…Recently it was shown that Puma (but not Noxa) is sensitive to caspase-3-dependent proteolytic destruction [5]. In line with these results, we found that caspase-3 processing in cells treated with the drug combination was associated with strongly reduced levels of Puma, but not Noxa.…”
Section: Discussionsupporting
confidence: 90%
“…Recently it was shown that Puma (but not Noxa) is sensitive to caspase-3-dependent proteolytic destruction [5]. In line with these results, we found that caspase-3 processing in cells treated with the drug combination was associated with strongly reduced levels of Puma, but not Noxa.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we noted that p21, PUMA and NOXA levels decreased with the onset of apoptosis. As these mediators can be cleaved by activated caspase-3,30 31 an additional layer of complexity needs to be considered when expression data is used as a surrogate marker of p53 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-mediated processing may be considered because of strong caspase 3 activation in CTCL cells. Caspase-mediated degradation of Mcl-1 (Wardle et al, 2011), XIAP (Muhlethaler-Mottet et al, 2008, and Puma (Hadji et al, 2010) has been reported in neutrophils, neuroblastoma cells, and Jurkat cells, respectively. Nevertheless, gene regulation appears as a major target of HDACi activity (Dickinson et al, 2010).…”
Section: Correlation Of In Vitro and Ex Vivo Datamentioning
confidence: 98%